Uranium-induced Cytotoxicity in HEK 293T Cells is reduced by a β-glucan type Exopolysaccharide produced by Enterobacter sp. YG4 - K. K. Nagaraj, A. B. Arun, P. D. Rekha (Journal of Applied Pharmaceutical Science, 2018)
Uranium-induced nephrotoxicity is a major health concern and countering it is essential. In this regard; a β-glucan type exopolysaccharide produced by Enterobacter sp. YG4 was tested for its capacity to reduce the uranyl nitrate-induced cytotoxicity in Human embryonic kidney cell line (HEK 293T). This exopolysaccharide at 0.5 mg/mL concentration was able to remove 80.94% of uranyl ions from its aqueous solution. Experiments with HEK 293T cells showed that the exposure to 0.05 mg/mL uranyl nitrate resulted in 22.13% cytotoxicity and treatment with YG4 exopolysaccharide could reduce the cytotoxicity of uranyl nitrate significantly. These results highlight the potential of this exopolysaccharide in counteracting the nephrotoxic effects of uranium.
Keywords: Uranium, Nephrotoxicity, Exopolysaccharide,&beta; -glucan.